Gene polymorphisms playing roles in pharmacokinetics and pharmacodynamics of buprenorphine: an overview - Kaya Akyüzlü, Dilek (Journal of Dependence, 2023)
Although buprenorphine is effective in the treatment of opioid use disorder, treatment failure rates are high among opioid users due to relapse and/or drop-out. This leads to significant costs to society in terms of health services and justice. The efficacy of pharmacotherapy for opioid use disorder is estimated to be between 60-70%. It is important to understand the individual characteristics of patients, such as genetic profile in detail to increase the effectiveness of treatment and reduce the high drop-out rates. It is widely accepted that there is an interaction between responsiveness to treatment and genetic variants that regulate the metabolism, mechanism of action and transport of drugs. Therefore, individualized treatment would be a good approach to improve treatment outcomes and also to facilitate longer periods of abstinence in opioid users at high risk of treatment failure. More studies are needed to understand the individualization of buprenorphine dose and the relationship between buprenorphine dose and efficacy in the treatment of opioid use disorder.